Effects of long cooling periods of the ear skin on the isolation and cultivation of bovine fibroblasts for use in nuclear transfer technique - Araújo, Jessica Maresch de (2020)
Dissertação (mestrado)—Universidade de Brasília, Faculdade de Agronomia e Medicina Veterinária, 2020.